Is it safe to incise skin by monopolar electrocautery? A comparative study - Thakkar, Nimesh B.; Patel, Pranav; Sonagra, Gautam (International Surgery Journal, 2019)
Background: The present study of evaluation of the use of electrocautery to incise the skin has been done to evaluate and assess basically. The advantages and disadvantages of the electrocautery to incise the skin when compared with that of scalpel. The results of the use of electrocautery on skin wound are then assessed to formulate the criteria for proper case selection for this procedure. Methods: A total of 100 patients were taken for this study. 50 patients underwent electrocautry monopolar mode incision (group A) who were compared with 50 scalpel incision patients (group B). Study was done from 01 January 2016 to 30 September 2017. Variables used in this study were complication like pain, lack of apposition and skin infection at the site of incision, pain, sinus formation and induration. This method was also evaluated with respect to following parameters: days of hospitalization, cosmetic result, rate of infection, wound apposition and requirement of secondary suturing. Results: As per our study, results are in favour of electrocautry by means of hemostasis. But we found that infection rate and complications are more with it. Moreover number of dressings required and hospital stay was also more with patient undergoing skin incision with electrocautry. Conclusions: For locally overlying healthy skin with no compromise of vascularity or any oedema and there is less fat, electrocautery use for skin incision can still be recommended for better cosmetic result and shorter healing time with less complication and rapid surgery.